Synthesis, Characterization, Antibiofilm and Anticancer Activity of New Ruthenium Complexes with 2,2'-bipyridine-4,4'-dicarboxamide - Kilincarslan, Sidika D.; Sahin, Cigdem; Mutlu, Dogukan; Nasirli, Farid; Arslan, Sevki; Dogan, Nazime Mercan (Letters in Organic Chemistry, 2022)
New ruthenium complexes bearing bipyridine ligands with different substituents (propyl, hexyl, isobutyl, and benzyl) were synthesized and characterized by MS, NMR, FTIR, and UV/Visible spectroscopy. Moreover, their cytotoxic, anti-carcinogenic, and anti-biofilm activities were evaluated. The electrochemical properties of the complexes have been investigated by cyclic voltammetry. The HOMO and LUMO energy levels of RuL1-RuL4 were found to be (-5.45 eV)-(-5.46 eV) and (-2.98 eV)-(-3.01 eV), respectively. Cytotoxic activities of ruthenium complexes were investigated in Caco-2, HepG2, and HEK293 cells. It was found that RuL3 showed a cytotoxic effect on cancer cells without affecting non-cancerous cells at applied doses. The presence of the benzyl group may increase the cytotoxic effect of RuL3 compared to other derivatives that contain the alkyl group. The apoptotic effect of the RuL3 derivative was determined by using Arthur image-based cytometer. It found that RuL3 induced apoptosis in Caco-2 (5-fold) and HepG2 (2-fold) cancer cells, respectively. All ruthenium complexes inhibited Staphylococcus aureus ATCC 29213 biofilm, but RuL3 had a more pronounced effect. Moreover, RuL3 had biofilm inhibition and biofilm degradation effect, while RuL1 and RuL4 demonstrated only biofilm inhibition. The fluorescent microscopy analysis confirmed the antibiofilm effect of ruthenium complexes. All of these results clearly showed that RuL3 showed cytotoxic and apoptotic effects on cancer cells.
Keywords: electrochemistry